THE INFLUENCE OF PHYSICAL STORE AND FOOD DELIVERY APPLICATION TOWARDS PURCHASE INTENTION IN FOOD AND BEVERAGES INDUSTRY - Cerry Marlencia; Fernando; Brigita Meylianti Sulungbudi (Sean Institute, 2023)
The background of this study refers to the importance of Physical Store especially in Food and Beverages Industry (Restaurants, Cafés, etc.). Physical Store used to be one of the important aspects that need to be fulfilled to run businesses in this industry as a market orientation strategy business. After the Food Delivery Application exist, the importance of Physical Store is starting to shift because businesses could start a business without having a specific location for their restaurant, café, and etc. In addition, the whole world experiencing a pandemic situation due to Covid-19 disease that emergence new rules that require people to social distancing. Because of these rules, people are limited to going out and start using Food Delivery Application more frequently. In hence, a lot of Food and Beverages businesses closed their physical store due to losses arising from the pandemic situation. This study aims to find out how the Physical Store and Food Delivery Application influence the Purchase Intention in Food and Beverages industry. This result study in line with the previous research from Torlak, Demir, & Budur (2019); Ryu Lee, & Kim (2012); Kincaid, et. al. (2010) that determines the influence of Physical Store towards Purchase Intention. Also, the previous research from Pitchay, et al. (2021); Wen, Pookulangara, & Josiam (2021); and Kaur et al. (2021) has supported this study accordance with the Influence of Food Delivery Applications towards Purchase Intention. As quantitative and explanatory research, the gathering data method is questionnaire spread to 100 people who ever bought a product from the same business through Physical Store and Food Delivery Application. This study uses the Multiple Linear Regression Analysis and the hypothesis have passed the T-Test and F-Test. The result determines Physical Store dimensions which are Accessibility, Cleanliness, Employee, Food and Service Quality, and Restaurant Ambience is significant, that means all the dimension still has influence for 0,090. Whereas for Food Delivery Application dimensions which are Core Value, Trust, and Price has influence to Purchase Intention for 0,337. Both of variables has influences 30,6% to the Purchase Intention. Other than that, the Food Delivery Application has a bigger influence than the Physical Store accordance with the processed data.